Privacy, Trust, and Manipulation in Online Relationships. Issue 2 (2nd April 2020) - Aïmeur, Esma; Sahnoune, Zakaria
Abstract: This work studies factors that influence personal information disclosure coming from vulnerable users who may adopt risky online behavior on social media. These users trust their online relationships and reveal confidential or sensitive information, causing damage to themselves and their relatives and friends. We carried a survey-based study on 1, 532 participants to see if they would reveal sensitive information when they have close online relationships whom they trust. The results led to several discoveries, especially concerning the factors affecting the disclosure in online relationships, and those affecting the attitude toward online manipulation. Moreover, this study attested a strong positive relation between disclosure issues and the user's attitudes toward manipulation. The latter which is affected by their online behavior and social interaction ties. In a nutshell, users attitudes toward manipulation may lead to self-disclosure on the one hand, and these attitudes could be identified through their social behavior on the other hand.